2017
DOI: 10.1038/s41598-017-16347-9
|View full text |Cite
|
Sign up to set email alerts
|

Calf Circumference as a Novel Tool for Risk of Disability of the Elderly Population

Abstract: Disability became increasingly common with age, and crude rates of disability were rising around the globe. The aim of this study was to investigate the association between calf circumference (CC) and disability in the U.S. elderly population. From the 1999–2006 National Health and Nutrition Examination Survey, a total of 4,245 participants with an age range of 60–84 years were included. Disability was defined as the total number of difficulties within the following 5 major domains of disability, such as activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
1
12
0
4
Order By: Relevance
“…Calf circumference is positively correlated with muscle mass, associated with nutritional status and disability, and recommended by the Asian Working Group for Sarcopenia as a screening tool for sarcopenia (31,69,70). Interestingly, our study found prevalence of small calf circumference was significantly lower in higher FMI and FM/FMI tertiles where the prevalence of sarcopenic obesity was also high.…”
Section: Discussionmentioning
confidence: 42%
“…Calf circumference is positively correlated with muscle mass, associated with nutritional status and disability, and recommended by the Asian Working Group for Sarcopenia as a screening tool for sarcopenia (31,69,70). Interestingly, our study found prevalence of small calf circumference was significantly lower in higher FMI and FM/FMI tertiles where the prevalence of sarcopenic obesity was also high.…”
Section: Discussionmentioning
confidence: 42%
“…Additionally, other research showed that CC might be positively connected to lower frailty index scores and higher functional performance . From the 1999–2006 NHANES, which contained 4245 older adults, CC might be an innovative tool to assess the disability risk in the older adult population . Furthermore, the result from a longitudinal survey on aging in Taiwan, which enrolled 2521 adults aged ≥65 years, showed that CC had better ability to predict emerging care need in the older Taiwanese population .…”
Section: Discussionmentioning
confidence: 99%
“…Calf circumference has been used as a simple proxy marker for skeletal muscle mass, sarcopenia, and nutritional status in clinical and community settings [ 14 , 15 , 16 , 17 , 18 ]. Furthermore, it has been shown to be effective in predicting subsequent disability, an emerging need for care, and mortality in older adults [ 43 , 44 , 45 ]. On analyzing a representative sample of older US adults (age range: 60–84 years) according to four anthropometric parameters (waist, arm, thigh, and calf circumferences), only calf circumference showed a significant (inverse) association with disability [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown to be effective in predicting subsequent disability, an emerging need for care, and mortality in older adults [ 43 , 44 , 45 ]. On analyzing a representative sample of older US adults (age range: 60–84 years) according to four anthropometric parameters (waist, arm, thigh, and calf circumferences), only calf circumference showed a significant (inverse) association with disability [ 44 ]. In the Taiwan Longitudinal Survey on Aging Study [ 45 ], calf circumference was a better predictor of an emerging need for care in older adults compared to BMI.…”
Section: Discussionmentioning
confidence: 99%